The new topical steroid ciclesonide is effective in the treatment of allergic rhinitis - Schmidt, Bernhard; Timmer, Wolfgang; Georgens, Anette Christiane; Hilt, Monika; Mattinger, Cathrine; Wurst, Wilhelm; Hörmann, Karl; Wehling, Martin (Journal of clinical pharmacology, 1999)
A randomized, placebo-controlled, double-blind crossover study was performed to investigate the efficacy of ciclesonide nasal spray in allergic rhinitis at the dose level of 200 μg per nostril. Twenty-four subjects (13 males, 11 females; median age: 28 years) with a history of allergic rhinitis but free of symptoms at screening entered the study. Ciclesonide and placebo were given for 7 days each with a washout period of at least 14 days in between. In both treatment periods, controlled intranasal allergen provocation with pollen extracts was performed on the 2 days before start of treatment (days −2 and −1) and on all treatment days (days 1 to 7) about 2 hours after administration of the study medication. At 5 and 30 minutes after each allergen provocation, rhinal airflow was measured by anterior rhinomanometry, and the subjective symptoms of obstruction, itching, and rhinorrhea were assessed by means of a standardized visual analog scale. Rhinal airflow improved significantly from day 5, while the subjective symptom of obstruction improved from day 2. Itching and rhinorrhea also improved significantly. The local and systemic tolerability of ciclesonide nasal spray was excellent. The results of this study clearly indicate that the new topical steroid ciclesonide is effective in the treatment of allergic rhinitis without producing local or systemic side effects.
Elektronische Reproduktion der Druck-Ausgabe 8. März 2013
Gesehen am 13.10.2022